Electronic Structure and Magnetism of 3d-Transition Metal Pnictides - Motizuki, Kazuko; Ido, Hideaki; Itoh, Tadaei; Morifuji, Masato; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book presents the results of investigations into the magnetic properties of 3d-transition metal compounds. In particular, it deals with 3d-metal pnictides (i.e., compounds containing phosphorus, arsenic, antimony or bismuth). Part I reports the experimental data together with phenomenological discussions from fundamental and application view points. Part II addresses how some of interesting behaviors mentioned in Part I can be explained on the basis of an itinerant electron picture. Band structures obtained by first-principle calculations are applied to introduce theories to calculate various properties such as susceptibility, magnetic ordering, and magnetic transitions, etc.
Experimental -- Basic Properties of 3-Pnictides -- Overview of Magnetic Properties of NiAs-Type (MnP-Type) and CuSb-Type Compounds -- Properties of the Compounds with NiAs-Type (MnP-Type) and CuSb-Type Structures -- Itinerant Electron Theory -- Electronic Band Structure and Magnetism of NiAs-Type Compounds -- Itinerant Electron Theory of Magnetism of CuSb-Type Compounds.
Keywords: Chemistry, Physical organic; Magnetism; Materials; Surfaces (Physics).; Materials Science; Structural Materials; Magnetism, Magnetic Materials; Characterization and Evaluation of Materials; Physical Chemistry